Synthesis, crystal X-ray diffraction structure, vibrational properties and quantum chemical calculations on 1-(4-(4-Fluorobenzamido)phenyl)-3-(4-fluorobenzoyl)thiourea - Saeed, Aamer (2010)
The 1-(4-(4-Fluorobenzamido)phenyl)-3-(4-fluorobenzoyl)thiourea species (1) has been synthesized and characterized by GC–MS, elemental analyses and 1H NMR and FTIR spectroscopy techniques. The crystal structure of the novel compound – having a benzamide moiety attached to a thiourea nucleus – has been determined by X-ray diffraction. The species crystallize in the triclinic space group P-1, Z = 4, with 2 molecules per asymmetric unit. Additionally there is one ethylacetate solvent molecule per asymmetric unit. The carbonyl and thiourea groups are almost planar and the conformation adopted by the C=S and the C=O double bonds is mutually antiperiplanar. Density functional theory methods have been applied to determine the conformational space around the central –C(O)NHC(S)NH– moiety. The vibrational properties have been studied by FTIR and FT-Raman spectroscopy along with quantum chemical calculations at the B3LYP/6-311+G* level of approximation.